2020
DOI: 10.20944/preprints202009.0362.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Artificial Intelligence (AI) and Poverty Reduction in the Fourth Industrial Revolution (4IR)

Abstract: Though the share of the world population living in extreme poverty declined to 10 percent in 2015, from 16 percent in 2010 and 36 percent in 1990, data shows that the world is not on track in achieving the target of less than 3 percent of people living in extreme poverty by 2030. Hence the study sought to investigate the influence of AI on poverty reduction. Using content analysis one of the unobtrusive research techniques, the study found out that, the availability of relevant data is making AI be able to del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…While governments might have different time frames and alternative AI policy objectives, the uptake of AI has been considered one of the key strategies to promote future competitiveness and resolve future societal challenges concerning economic growth as well as noneconomic issues, such as poverty, sustainability, health, and human well‐being in both developed and developing countries. For example, algorithm‐based systems have been developed and applied to identify areas in which shortages of agricultural products are expected, and to help governments take preventive actions to eradicate poverty in developing countries (Bennington‐Castro, 7; Mhlanga, 2020).…”
Section: Objectives Sought In Pursuing Inclusive Ai For Social Goodmentioning
confidence: 99%
See 1 more Smart Citation
“…While governments might have different time frames and alternative AI policy objectives, the uptake of AI has been considered one of the key strategies to promote future competitiveness and resolve future societal challenges concerning economic growth as well as noneconomic issues, such as poverty, sustainability, health, and human well‐being in both developed and developing countries. For example, algorithm‐based systems have been developed and applied to identify areas in which shortages of agricultural products are expected, and to help governments take preventive actions to eradicate poverty in developing countries (Bennington‐Castro, 7; Mhlanga, 2020).…”
Section: Objectives Sought In Pursuing Inclusive Ai For Social Goodmentioning
confidence: 99%
“…AI technologies have also advanced smart farming decisions, for example, in crop breeding and crop management, as shown in the FarmView project; this project helps in choosing crops, such as sorghum, that are best suited for certain geographical locations in many Asian and African developing countries (Bennington‐Castro, 2017; Schmidt, 2019). AI has also been widely used to map poverty, for example, at the Qatar Computing Research Institute (QCRI) at Hamad Bin Khalifa University, which initially worked for the UNICEF Innovation and Thinking Machine, a Philippines‐based start‐up (Bush, 2019; Mhlanga, 2020).…”
Section: Objectives Sought In Pursuing Inclusive Ai For Social Goodmentioning
confidence: 99%
“…Step 8: Analytical findings The finding from the selected study indicated that artificial intelligence has a greater impact the human life in the revolutionary era (Mhlanga, 2020). This is because it is a composite of identifying the potential benefits based on reducing the harm to intro visual life especially related to stress and negative carbonate thoughts (Rachmadtullah et al, 2020).…”
Section: Figure 3: Funnel Chart Studies Relevancementioning
confidence: 99%
“…It also indicated that artificial intelligence is highly functional in different educational domains identifying the different disciplines has their own policies theories and practical's (Mosteanu, 2020). Therefore, the artificial intelligence provides every new information based on validity (Mhlanga, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to highlight that direct access and use of financial resources is not only the avenue through which financial inclusion can benefit people, but there are other indirect benefits associated with financial inclusion like consumption smoothening and being cushioned from shocks like natural disasters and other economics challenges (Cámara andTuesta, 2018, Chibba, 2009). Empirically, scholars believe financial inclusion should be embraced as a complement to traditional ways of addressing social challenges like poverty and inequality (Chibba 2009, Mhlanga 2020a, Mhlanga 2020b.…”
Section: Introductionmentioning
confidence: 99%